The Serum ionized calcium , thrombin time (TT), fibrinogen (FIB) after Heparin and Sodium Citrate Anticoagulation in Children with Sepsis : serum iCa2+ , thrombin time (TT), fibrinogen (FIB) - Wang, Huixia (Journal of Medical Biochemistry, 2025)
Introduction: it aimed to compare the anticoagulant effect and bleeding risk of systemic heparin anticoagulation and local sodium citrate anticoagulation in continuous renal replacement therapy(CRRT) in children with sepsis in the intensive care unit (ICU). Method: the clinical data of 96 children with sepsis in ICU treated in Northwest Women’s and Children’s Hospitalfrom January 2021 to January 2024 were retrospectively analyzed. The children were divided into control group (CG) and observation group (OG). The coagulation function indexes, blood purification treatment effect, and the incidence of bleeding events during CRRT were compared. Result: after treatment, activated partial thromboplastin time (APTT), prothrombin time (PT), and thrombin time (TT) were visibly increased, while fibrinogen (FIB) was visibly decreased; APTT, PT, and TT increased visibly, and FIB decreased visibly in the OG;the results of pH, HCO3-, Na+ were visibly different from those before treatment; creatinine (Cr) and urea nitrogen (BUN) were visibly lower, and the decrease of Cr and BUN in the OG was slightly higher as against the CG; the iCa2+ was visibly higher in the OG as against the CG; the incidence of bleeding in the OG was 27.08%, which was visibly lower than 35.42% in the CG (all P < 0.05). Conclusion: local sodium citrate anticoagulation shows a good anticoagulation effect in CRRT in children with sepsis in ICU, and the bleeding risk is relatively low.